Advancements in Digital Workflows for 3D-Printed Maxillofacial Soft Prostheses: Exploring Design and Materials in Direct Additive Manufacturing: A Scoping Review - Cristian Ioan Tarba; Mircea Alexandru Cristache; Ioana Medeea Baciu; Corina Marilena Cristache; Oana Elena Burlacu Vatamanu; Luminita Oancea (Applied Sciences, 2025)
The treatment of maxillofacial defects presents significant challenges due to the complexity of facial anatomy and the diversity of affected tissues. Traditional workflows are labor-intensive, costly, and limited in customization. Recent advancements in fully digital workflows and direct 3D printing technologies offer new possibilities for improving the fit, aesthetics, and efficiency of prosthetic manufacturing. This scoping review aims to evaluate the current state of direct 3D printing for maxillofacial soft prostheses, assess material properties and biocompatibility, and identify challenges and future directions in this field. Methods: A comprehensive search of PubMed and Scopus databases, along with a manual search of relevant journals, was conducted to identify studies published up to December 2024. Articles focusing on direct 3D printing of maxillofacial soft prostheses were included, while studies involving traditional or mold-based workflows, ocular prostheses, and literature reviews were excluded. Data on materials, manufacturing techniques, and clinical outcomes were extracted and analyzed. Results: Out of 898 articles screened, 11 were included, 5 of which were in vivo studies (case reports). The additive manufacturing methods used in these case reports were Drop-on-Demand (DoD) silicone printing and PolyJet technology. Conclusions: Fully digital workflows and direct 3D printing technologies show promise for advancing maxillofacial prosthesis manufacturing. However, the absence of dedicated software, biocompatible materials, and medium- to long-term clinical evaluations highlight significant research gaps. Future research should focus on material development, workflow optimization, and clinical validation to enable widespread clinical adoption.